MENSINERGIKAN PEMBERDAYAAN: PENGALAMAN LAPANGAN PELAKSANAAN PEMBERDAYAAN KOMUNITAS PKPU DI PASAR MAMPANG JAKARTA SELATAN - Masdariah, Masdariah; Fachrezi, RM. Fachri (Jurnal Kommunity Online, 2023)
The increase in poverty caused by the prolonged economic crisis has made the small business sector go out of business due to competition with large entrepreneurs, while relatively small capital and poor management make small businesses unable to develop their business to the fullest. This article concludes that the implementation of approaches in community empowerment requires strategies to encourage success in the program, namely through training strategies, provision of revolving funds, profit-sharing funds, joint venture funds, and BMT funds are the findings of field research. This strategy is expected to be able to change the condition of the poor to become more empowered, through the skills of community workers to the target community.